Withstanding the Effect of Industry 4.0: The Role of High Performance Work System and Management Philosophy - Houcine Meddour; Iyanda Ismail Abdulssalaam; Abdul Halim Abdul Majid (International Journal of Supply Chain Management, 2020)
Coping with challenges posed by the extant IR 4.0 demands that small businesses should provide ‘added-value’ services, and products, or high quality and innovative products and services which could be possible through strategic development of employees.  Drawing upon the findings of the extant literature, HPWS which is aligned with befitting management philosophy would help achieve enduring and enhanced performance culminated in provision of innovative goods and services. To offer context-based empirical insights on this issue, this study investigated the moderating role of management philosophy in the HPWS-performance nexus. The present study employed cross-sectional research approach in which data were collected from a sample of 518 of SME managers in Nigeria. Partial Least Squares Method (PLS) algorithm and bootstrapping technique were used to test the study’s hypotheses. Using product indicator approach, moderating effect of management philosophy was estimated. The findings signified a positive effect of HPWS on SME performance, and management philosophy was found to interact negatively with HPWS in enhancing performance. This result portrays presence of mismatch between managers’ philosophies and HPWS. Overall, the findings of the present study accentuate that HPWS which is aligned with befitting management philosophy would help achieve enduring and enhanced performance culminated in provision of innovative goods and services, with which the challenges posed by IR 4.0 will be withstood. Lastly, implications, limitations and suggestions for future research are discussed